Gallium-68: methodology and novel radiotracers for positron emission tomography (2012–2017). (1st August 2018) - Tanzey, Sean S; Thompson, Stephen; Scott, Peter JH; Brooks, Allen F
Commercial 68 Ge/ 68 Ga generators provide a means to produce positron emission tomography agents on site without use of a cyclotron. This development has led to a rapid growth of academic literature and patents ongallium-68 ( 68 Ga). As 68 Ga positron emission tomography agents usually involve a targeting moiety attached to a metal chelator, the development lends itself to the investigation of theragnostic applications; the 68 Ga-based diagnostic is utilized to determine if the biological target is present and, if so, a therapeutic isotope (e.g., 177 Lu, 225 Ac) can be complexed with the same scaffold to generate a corresponding radiotherapeutic. This review considers patents issued between 2012 and 2017 that contain a 68 Ga-labeled molecule indexed by Chemical Abstract Services (a division of the American Chemical Society).